Effectiveness of Education Program on Health Care Workers’ Practices toward Waste Management in Primary Health Care Centers - shabib, Hashim; Khalifa, mohammed (Iraqi National Journal of Nursing Specialties, 2016)
Objective(s): The aim of this study is to determine the effectiveness of education program on Health Care Workers’ practices toward Primary Health Care Centers waste management and to identify the relationship between these practices and the demographic characteristics of the health workers. Methodology: A quasi- experimental design (pre-post tests) has been used in the present study for the period of November 16th 2014 to June 22nd 2015 .The allocated sample in the present study is consisted of (60) health care worker. The sample was randomly divided into two groups of (30) health care workers each. The study group consisted of (30) health care worker who are exposed to the program. The group that is not exposed to the program was considered the control group. The data are collected through use of A practice checklist for health care workers’ was use prior to performing educational program during work time. The practice checklist for health care workers’ was composed of (30) items . A practice test is used for pre- education and post-education immediately. Results: All the health care workers in the study group work in PHCs are having good practices post the program implementation and perform principles of waste management practices in ideal way.. Recommendations: Availability of scientific using journal or books in Arabic language and emphasis on the importance of motivation for the health care workers to this practices in the medical waste management.